2002
DOI: 10.1002/app.11334
|View full text |Cite
|
Sign up to set email alerts
|

Films of PLLA/PHBV: Thermal, morphological, and mechanical characterization

Abstract: Blends of poly(l-lactic acid)/poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PLLA/PHBV), both semicrystalline polymers, were prepared in different compositions (100/0, 80/20, 60/40, 50/50, 40/60, 20/80, and 0/100) and characterized by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), scanning electron microscopy (SEM), polarized light microscopy (PLM), and tensile tests. Although PLLA/PHBV blends do not present clear phase separation by SEM, the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
85
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 16 publications
14
85
2
4
Order By: Relevance
“…This gradual decrease of the T g of PLA phase can be understood as an increase of compatibility of PLA/PHBV blends due to the presence of the oLA, miscible with both PLA and PHBV. The cold crystallization temperature of PLA is decreased from 119 to 105°C with the addition of PHBV, as already observed by previous authors [15,16,45], and is not influenced by oLA addition. The PLA degree of crystallinity also remains extremely low in every case (<5%).…”
Section: Films Characterization 331 Thermal Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…This gradual decrease of the T g of PLA phase can be understood as an increase of compatibility of PLA/PHBV blends due to the presence of the oLA, miscible with both PLA and PHBV. The cold crystallization temperature of PLA is decreased from 119 to 105°C with the addition of PHBV, as already observed by previous authors [15,16,45], and is not influenced by oLA addition. The PLA degree of crystallinity also remains extremely low in every case (<5%).…”
Section: Films Characterization 331 Thermal Analysissupporting
confidence: 87%
“…Zhang et al [21] found that melt blended samples exhibited greater compatibility than those prepared by solvent casting at room temperature, possibly due to a transesterification reaction between PHB and PLA occurring at high temperature. This transesterification, or more generally the presence of specific interactions between the two polymers, has been evidenced by many other authors [14,15,[22][23][24], especially for blends containing a low amount of PHB(V). For such PLA/PHBV blends (typically weight fractions of 90%/10%), Gerard and Budtova [22] observed a peculiar morphology, with very small PHBV nodules (about 400 nm) well dispersed in PLA matrix, with increased adhesion at the interface, presumably explaining the increase of ductility (elongation at break of 200% when tested immediately after sample preparation) measured for this composition by the authors.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Its properties are known to depend on hydroxyvalerate (HV) content [10]. At very low HV content, PHBV is similar to conventional petrochemical thermoplastics, such as polypropylene, in terms of melting temperature, crystallinity, and tensile strength [11][12][13][14][15]. Most of literature agrees on immiscibility of PLA and PHBV [16][17][18][19].…”
mentioning
confidence: 99%
“…Several factors determine the degradation rate of those polymers, including the site of the implant, the chemistry and stereoisomeric composition of the material, crystallinity, size and morphology of the scaffold, external pH medium and other parameters 7 . Thus, the in vitro and in vivo degradation studies have been proposed to establish relationships among those factors 8,9 . Within the many types of bioresorbable material applications, porous morphology is the preferred ones.…”
Section: Introductionmentioning
confidence: 99%